Origin of magnetoresistance across the martensitic transformation: formation of phase fraction. (12th March 2020) - Modak, M; Ray, Mayukh K; Mondal, S; Maji, B; Bagani, K; Bhattacharyya, A; Banerjee, S
Abstract: The influence of martensite and austenite phase volume fractions on the magnetoresistance have been studied across the first order martensite transformation of the Ni44 Cu2 Mn43 In11 compound. The different phase volume fractions are calculated by measuring the resistivity as a function of temperature and magnetic field. Our experiment reveals that the field-induced austenite phase fraction ( f IA ) at any temperature depends on the availability and instability of the martensite phase fraction ( f M ) at that temperature. This f IA is found to contribute most significantly to the observed large magnetoresistance (MR), while the contributions from parent martensite and austenite phase fractions are negligible. It has been found that the MR does not depend linearly on the f IA . On application of a magnetic field, the ascending and descending branch of the f IA follows a different power law, giving rise to hysteresis in the MR.